Predictors of Sleep Quality and Sleepiness in the Iranian Adult: A population Based Study - Batool Tirgari; Mansooreh Azzizadeh Forouzi; Sedigheh Iranmanesh; Sedigheh Khodabandeh Shahraki (Shahid Sadoughi University of Medical Sciences, 2013)
Introduction: Information on the sleepiness and sleep quality is limited for Asians. This study was conducted to determine the prevalence of sleepiness and sleep quality among the adult population in Iran. Materials and Methods: This is a descriptive and explorative design study in which 1100 participants randomly selected from the Kerman city population in South -East of Iran. Using two questionnaires, Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale (ESS), sleep quality and prevalence of sleepiness of samples was assessed. Results: Our findings showed that the prevalence of sleepiness was 34.3%. Moreover, daytime sleepiness correlated with marriage status (p= 0.048), work shift (p= 0.0001), and work hours (p= 0.004). 57.5% of the participants reported that they have poor sleep quality. The mean and standard deviation of PSQI component scores are widely ranged. The lowest score belonged to "hypnotic medication use" component (mean= 0. 38), and the highest score belonged to "sleep duration" component (1.14 ± 0.90). Sleep quality also was found to be correlated with age (p=0.045), work shift (p= 0.0001), and work hours per day (p= 0.015). Pearson correlation coefficient showed a significant correlation between sleep quality and sleepiness (p=0.0001) among participants. According to Binary logistic regression results, the risk of sleepiness among participants with poor sleep quality was 4.2 times more than that among those who had good sleep quality. Conclusions: The results indicate almost high prevalence of poor sleep quality and sleepiness among our study population. Therefore, improving the quality of population's sleep requires cultural preparation and public education through the media and also by well-educated nurses.